Nanostructured glass-ceramic materials from glass waste with antimicrobial activity - Caland, Juliani P. (2024)
Modern consumption patterns have led to a surge in waste glass accumulating in municipal landfills, contributing to environmental pollution, especially in countries that do not have well-established recycling standards. While glass itself is 100% recyclable, the logistics and handling involved present significant challenges. Flint and amber-colored glass, often found in high quantities in municipal waste, can serve as valuable sources of raw materials. We propose an affordable route that requires just a thermal treatment of glass waste to obtain glass-based antimicrobial materials. The thermal treatment induces crystallized nanoregions, which are the primary factor responsible for the bactericidal effect of waste glass. As a result, coarse particles of flint waste glass that undergo thermal treatment at 720 °C show superior antimicrobial activity than amber waste glass. Glass-ceramic materials from flint waste glass, obtained by thermal treatment at 720 °C during 2 h, show antimicrobial activity against Escherichia coli after just 30 min of contact time. Laser-induced breakdown spectroscopy (LIBS) was employed to monitor the elemental composition of the glass waste. The obtained glass-ceramic material was structurally characterized by transmission electron microscopy, enabling the confirmation of the presence of nanocrystals embedded within the glass matrix.